Forecasting the Arrival of the Next Pandemic Wave – Modeling and Tools - DYMORA, PAWEŁ; MAZUREK, MIROSŁAW; GÓRNIAK, PAULINA (Journal of Education, Technology and Computer Science, 2024)
The scope of the paper is to review the literature on data analysis and visualization in the context of the COVID-19 pandemic and to describe the different tools and methods used in this type of analysis. Examples of the use of these tools in practice and their limitations will also be presented. The paper concludes with conclusions and recommendations for the use of data analysis and visualization to better understand the COVID-19 pandemic and to predict the arrival of future pandemic waves.An important feature of the article is the possibility of a broad overview of modelling possibilities and the selection of appropriate frameworks and tools which can be used in the educational process of data analysis for students for in-depth study and prediction of trends and data, in particular of such important issues as the evolution of pandemic.